Anti-arthritic and toxicological evaluation of ethanolic extract of Alternanthera bettzickiana in rats - Manan, Maria; Saleem, Uzma; Ahmad, Bashir; Aslam, Nosheen; Anwar, Asifa; Zafar, Aimen (Frontiers in Pharmacology, 2022)
A practice was occurred from the decades in the developing countries, that these countries mostly used medicinal plants for therapeutic purposes due to its low cost and less toxicity. The current study was designed to evaluate the safety and anti-arthritic potential of A. bettzickiana ethanolic extract (ABEE). Acute oral toxicity (OECD 425) was performed for safety evaluation. Limit test was used to find out the LD50 value. For acute oral toxicity study dose of “2000 mg/kg” of ABEE was given orally to the treatment group and control group received distilled water at a rate of 10mL/kg. Biochemical, hematological, and histopathological analyses were performed after 14 days. Formaldehyde 2% w/v solution was injected via i.p. the route to rats of all groups to prepare the arthritic model. Five groups were divided into control (D.H2O), Standard (Diclofenac) and other three received the plant extract at dose levels of 125mg/kg. 250mg/kg and 500mg/kg respectively. Treatment was continued for 10 days. Paw diameter, hematological and biochemical variables were quantified. ELISA was performed for the estimation of inflammatory cytokines. In acute oral toxicity study no mortality and morbidity were observed so LD50 of this plant was greater than 2000 mg/kg. ABEE decreased the paw diameter with the restoration of hematological and biochemical changes. SOD and CAT levels were increased while decreased the MDA, NO, TNF-α, and IL-6 levels in arthritic rats. It is concluded that the use of A.bettzickiana is less toxic and can be used for the treatment of arthritis.